Guidance and support of women in engineering programs at Universidad Tecnologica de Bolivar (2023)
Gender equality is one of the sustainable development goals. In STEM areas, it is a requirement to expand and improve women's careers. To increase the participation of women in STEM it is not enough to attract more young women to these programs. It is necessary to provide orientation during the academic programs and ensure safe and rewarding environments so that women can succeed in their studies. The Faculty of Engineering of Universidad Tecnológica de Bolívar has gender gaps in most of its programs and several strategies are being implemented to overcome this situation. This paper analyzes five factors to guide and support women in engineering programs: academic success, protection of women, scholarships and financial assistance, international mobility, and leadership. We present several activities and strategies developed in the last three years in these five factors. The impacts of these strategies cannot be evaluated yet, but we expect that they can improve the well-being of women in engineering and contribute to the reduction of the gender gaps. © 2023 IEEE.